Seed Halopriming: A Promising Strategy to Induce Salt Tolerance in Indonesian Pigmented Rice - Purwestri, Yekti Asih; Nurbaiti, Siti; Putri, Sekar Pelangi Manik; Wahyuni, Ignasia Margi; Yulyani, Siti Roswiyah; Sebastian, Alfino; Nuringtyas, Tri Rini; Yamaguchi, Nobutoshi (2023)
Unfavorable environmental conditions and climate change impose stress on plants, causing yield losses worldwide. The Indonesian pigmented rice (Oryza sativa L.) cultivars Cempo Ireng Pendek (black rice) and Merah Kalimantan Selatan (red rice) are becoming popular functional foods due to their high anthocyanin contents and have great potential for widespread cultivation. However, their ability to grow on marginal, high-salinity lands is limited. In this study, we investigated whether seed halopriming enhances salt tolerance in the two pigmented rice cultivars. The non-pigmented cultivars IR64, a salt-stress-sensitive cultivar, and INPARI 35, a salt tolerant, were used as control. We pre-treated seeds with a halopriming solution before germination and then exposed the plants to a salt stress of 150 mM NaCl at 21 days after germination using a hydroponic system in a greenhouse. Halopriming was able to mitigate the negative effects of salinity on plant growth, including suppressing reactive oxygen species accumulation, increasing the membrane stability index (up to two-fold), and maintaining photosynthetic pigment contents. Halopriming had different effects on the accumulation of proline, in different rice varieties: the proline content increased in IR64 and Cempo Ireng Pendek but decreased in INPARI 35 and Merah Kalimantan Selatan. Halopriming also had disparate effects in the expression of stress-related genes: OsMYB91 expression was positively correlated with salt treatment, whereas OsWRKY42 and OsWRKY70 expression was negatively correlated with this treatment. These findings highlighted the potential benefits of halopriming in salt-affected agro-ecosystems. Â© 2023 by the authors.